Silibinin improved the function of T cells in peripheral blood mononuclear cells (PBMCs) co-cultured with U-87 MG cell line - Banafshe Abadi; Jahangir Abdesheikhi; Farnaz Sedghy; Merat Mahmoodi; Hossein Fallah (Mashhad University of Medical Sciences, 2024)
Objective: Silibinin has exhibited antitumor activities. However, there are few reports about the immunomodulatory properties of silibinin on T lymphocyte function in the tumor microenvironment. Here, we determined the effects of silibinin on T cells of peripheral blood mononuclear cells (PBMCs), cultivated alone or with a human cell line of glioblastoma (U-87 MG).Materials and Methods: The proliferation of T lymphocytes was assessed by MTT test in the presence of silibinin (15 and 45 µM). Also, total antioxidant capacity (TAC), the activity of superoxide dismutase-3 (SOD3), and the levels of two cytokines interferon gamma (IFN-γ) and tumor growth beta (TGF-β) were compared between treated and untreated PBMCs alone or co-cultured with U-87 cells.Results: According to our results, silibinin raised the TAC levels and SOD3 activity in the PBMCs and in the co-culture condition. Moreover, silibinin-treated PBMCs showed higher IFN-γ levels and lower TGF-β levels. Interestingly, silibinin protected PBMCs against the U-87-induced suppression.Conclusion: Altogether, these results proposed the immunomodulatory potential of silibinin on T cells of PBMCs, as well as its partially protective effects on PBMCs against the suppression induced by U-87 MG cells.